Perancangan Sistem Informasi Pengadaan Bahan Baku Menggunakan Model Waterfall untuk Meningkatkan Efisiensi Sistem Purchasing (Studi Kasus: UD La Riz Mebel) - Khoirunniam, Alan; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The manual raw material procurement system at UD La-Riz Mebel has caused various operational inefficiencies, including 23 stockout incidents per semester, overstock losses of Rp 20,450,000, order delays reaching 41%, and a recording error rate of 19%. This study aims to design a raw material procurement information system using the Waterfall model to enhance purchasing efficiency. The research methods include field observations, in-depth interviews, documentation studies, and system requirements analysis. System design follows the Waterfall phases: requirements analysis, system design using DFD, ERD, and database modeling, prototype implementation, and black-box testing. The results show that the proposed system reduces purchasing process time from 2.5 days to 0.5 days, decreases recording errors to 2%, reduces stockouts by 83%, and lowers overstock costs by 79%. Functional testing achieved a 100% success rate, while User Acceptance Testing scored 4.73 out of 5. The system significantly improves data accuracy, interdepartmental coordination, and overall operational efficiency.